Cardiovascular safety of Janus kinase inhibitors in patients with rheumatoid arthritis: systematic review and network meta-analysis - Wei, Qige; Wang, Hui; Zhao, Jianglin; Luo, Zhongping; Wang, Chufeng; Zhu, Chunmei; Su, Na; Zhang, Shengzhao (Frontiers in Pharmacology, 2023)
Janus kinase (JAK) inhibitors have emerged as a progressively utilized therapeutic approach for the management of rheumatoid arthritis (RA). However, the complete determination of their cardiovascular safety remains inconclusive. Hence, the primary objective of this network meta-analysis is to meticulously assess and juxtapose the cardiovascular risks linked to distinct JAK inhibitors employed in RA patients.Methods A systematic review and network meta-analysis were meticulously conducted, encompassing a collection of randomized controlled trials (RCTs) that focused on investigating the incidence of major adverse cardiovascular events (MACE) and all-cause mortality associated with Janus kinase (JAK) inhibitors administered to patients with rheumatoid arthritis (RA).Extensive exploration was performed across multiple electronic databases, incorporating studies published until March 2023. To be included in this analysis, the RCTs were required to involve adult participants diagnosed with RA who received treatment with JAK inhibitors. To ensure accuracy, two authors independently undertook the selection of eligible RCTs and meticulously extracted aggregate data. In order to examine the outcomes of MACE and all-cause mortality, a frequentist graph theoretical approach within network meta-analyses was employed, utilizing random-effects models. Thid study has been registered on PROSPERO under the reference CRD42022384611.Findings A specific selection encompassing a total of 14 meticulously chosen randomized controlled trials was undertaken, wherein 13,524 patients were assigned randomly to distinct treatment interventions. The analysis revealed no notable disparity in the occurrence of major adverse cardiovascular events (MACE) between the interventions and the placebo group. However, in comparison to adalimumab, the employment of JAK inhibitors exhibited an association with higher rates of all-cause mortality (odds ratio [OR]: 1.7, 95% confidence interval [CI]: 1.02-2.81). This observed increase in risk primarily stemmed from the usage of tofacitinib (OR: 1.9, 95% CI: 1.12-3.23). None of the other JAK inhibitors exhibited a statistically significant variance in all-cause mortality when compared to adalimumab.Interpretation Our study suggests that JAK inhibitors may not increase the risk of MACE in RA patients but may be associated with a higher risk of all-cause mortality compared to adalimumab, primarily due to tofacitinib use. Rheumatologists should carefully consider the cardiovascular risks when prescribing JAK inhibitors, particularly tofacitinib, for RA patients.